Interleukin-2 downregulates hepatitis B virus gene expression in transgenic mice by a posttranscriptional mechanism. - Guilhot, S (1993)
We have recently demonstrated that tumor necrosis factor alpha (TNF-alpha) and interleukin-2 (IL-2) downregulate the hepatic steady-state content of hepatitis B virus (HBV) mRNA in vivo in HBV-transgenic mice and that the IL-2 effect is mediated by TNF-alpha. In the current study, we demonstrate that IL-2-induced downregulation of hepatic HBV 2.1-kb mRNA is not due to changes in the transcription rate or the intranuclear maturation or export of this transcript but that it is selectively and profoundly depleted from the cytoplasm of the liver cells in vivo following IL-2 administration. Collectively, these results suggest that IL-2 alters the steady-state content of hepatic HBV mRNA by a posttranscriptional mechanism in vivo, that this effect is mediated by TNF-alpha, and that it probably reflects increased cytoplasmic degradation of the viral transcript.